2016
DOI: 10.1080/10720537.2016.1238789
|View full text |Cite
|
Sign up to set email alerts
|

Meaning Coconstruction in Group Counseling: The Development of Innovative Moments

Abstract: This study discusses a model of group counseling, the narrative mediation path (NMP), which is a unique narrative, multimodal approach that combines four narrative modes (metaphoric, iconographic, writing, and bodily) and the narrative group. The purpose of the NMP is to foster reflexive processes with underachieving university students and to improve their academic performance. The study analyzes a single case of group counseling for seven underachieving economics students at an Italian university and the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
3
11
0
1
Order By: Relevance
“…There have been some efforts to establish an IM coding for groups (e.g. Esposito, Ribeiro, Alves, Gonçalves, & Freda, ) which are setting a new ground for a coding manual for groups. Likewise, replication efforts are being made with bigger samples and different therapeutic models such as Barlow's UP (ongoing study) and psychodynamic therapy (Nasim et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…There have been some efforts to establish an IM coding for groups (e.g. Esposito, Ribeiro, Alves, Gonçalves, & Freda, ) which are setting a new ground for a coding manual for groups. Likewise, replication efforts are being made with bigger samples and different therapeutic models such as Barlow's UP (ongoing study) and psychodynamic therapy (Nasim et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous outcome measures (Esposito, Ribeiro, et al, 2016) suggested that the group was effective in improving students’ academic performance, as there was a significant increase in the ECTS ( Z = −2.201, p = .028) and the number of examinations passed ( Z = −2.214, p = .027) one year after the counseling concluded.…”
Section: Methodsmentioning
confidence: 94%
“…The aim was to investigate young people's experience because they are the most fragile group due to their difficulty staying home and apart from their peers and because they are, at the same time, the most potentially dangerous people due to their urge to gather in groups. Therefore, storytelling was used as a tool to collect their stories and to probe their meaning and symbolization, developing their reflectivity (Esposito et al, 2017 ; Salvatore et al, 2018 ). In fact, in our case, in line with the mission of community psychology to give voice to young people, among the most affected people by the pandemic's social implications, we asked our students to freely express their thoughts and emotions related to their lockdown experience.…”
Section: Methodsmentioning
confidence: 99%